The changing German voter - Schmitt-Beck, Rüdiger; Rossteutscher, Sigrid; Schoen, Harald; Wessels, Bernhard; Wolf, Christof (Oxford scholarship online, 2022)
Over the past half century, the behaviour of German voters has changed profoundly - at first rather gradually, but during the last decade at accelerated speed. Electoral decision-making has become much more volatile, rendering election outcomes less predictable. Party system fragmentation intensified sharply. The success of the AfD put an end to Germany's exceptionality as one of the few European countries without a strong right-wing populist party. Utilizing a wide range of data compiled by the German Longitudinal Election Study, the book examines changing voters' behaviour in the context of changing parties, campaigns, and media during the period of its hitherto most dramatically increased fluidity at the 2009, 2013, and 2017 federal elections.
Keywords: Voting : Germany : History : 21st century; Elections : Germany : History : 21st century; Germany : Politics and government : 1990-